Arduino Uno-Based Fire Alarm System - Nur Asmi Rahmawati; Hermansyah, Hermansyah (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
Fire is a disaster that can cause significant losses to life and property. Therefore, the development of an effective fire alarm system is essential in order to protect safety and security. This research aims to develop an